Cultivating organizational performance through the performance measurement systems: Role of psychological empowerment and creativity - Zhang, Lu; Kim, Dalgon; Ding, Shusheng (Frontiers in Psychology, 2023)
Interactive performance measurement systems (PMSs) play a critical role in shaping individual behaviour and performance. To identify the underlying mechanism of how PMSs enhance organisational performance, a proposed model was constructed to investigate psychological empowerment and employee creativity as possible mediating variables. Based on a sample of 211 managers from Chinese organisations, a partial least squares structural equation modelling (PLS-SEM) approach was used to examine the mediating effect presented in the aim. Interactive use of PMS has a positive and direct impact on psychological empowerment. Psychological empowerment positively influences creativity, which in turn positively influences organisational performance. The findings also show that psychological empowerment and creativity mediate the impacts of interactive use of PMS on organisational performance. Our study highlights the role of PMSs, and how to use them interactively in turbulent environments. Particularly, we demonstrate that interactive use of PMS is important for facilitating a manager’s sense of psychological empowerment and fostering creativity, which in turn contributes to better performance and greater competitive advantages.